Mechanically robust hydrophobic bio-based epoxy coatings for anti-corrosion application - Zheng, Shunli (2020)
Corrosion of aluminum and its alloys causes serious problems to our daily life. As a common method for corrosion protection, epoxy resin has been widely used as the coating material due to its easy processability and excellent properties. However, its high water absorption and brittleness, as well as the usage of volatile organic solvents during coating preparation, has limited its applications in some areas. In this study, we reported an environmentally friendly hydrophobic coating based on bio-epoxy using water as the only solvent during the preparation. The coating was fabricated by introducing superhydrophobic SiO 2 nanoparticles, a hydrophobic curing agent, and hexadecyltrimethoxysilane into an isosorbide-based epoxy resin via a one-step spin coating process. The coating exhibits high hydrophobicity with a water contact angle (CA) of 134 ± 3°. This as-prepared coating is found to have good mechanical robustness against sands erosion: it maintained a high water repellence with the CA of 146 ± 2° after sands erosion for 30 s. In addition, the as-obtained coating shows a one-order of magnitude reduction in the corrosion current density (J corr ), a positive shift of the corrosion potential (E corr ) from −1.008 V to −0.747 V, and an inhibition efficiency of 92%.